The impact of organizational dynamic capability on collaborative innovation: A supply chain perspective - WANG, Xiangdong (Institutional Knowledge at Singapore Management University, 2024)
Innovation capability is one of the most important competitive advantages of the firms, and fully collaborating with partners in the supply chain to form an innovation alliance has been proven can effectively promote the firm’s innovation performance. This research apply case study on China sportswear supply chain with a mixed method, aims to disclose the innovation Black-box and reveal the influencing factors and its mechanism. The study consists of two parts, Study 1 is semi-structured interviews with 32 industry experts, through the analysis of the interview records, we figured out what factors the industry experts believe it can improve the collaborations with partners and promote innovation performance. Study 2 is based on the findings from study 1, designed a questionnaire survey, distributed to the employee and managers in the sportswear supply chain. Based on 300 valid answers of the survey, a quantitative analysis was conducted to study the interaction between various variables and proven or refute the research hypotheses. The key findings of this study include: 1. It is proven that the geographical distance between the partners has a significant positive influence on the innovation collaboration and enhances innovation performance. 2. For the innovations it requires functional revolutions on the product technical, the concentration of the firm’s internal innovation capability is more important than seeking external collaborations. As for non-functional innovation, like appearance design or marketing innovation, a high level of external cooperation with partners can significantly promote innovation performance. Based on this, we further analyzed and came to the practical suggestions: Innovation work requires high-frequency and in-depth communication, requires a high degree of integration of knowledge and technology, and requires efficient concentration of innovation resources. Especially, for revolutionary innovations with underlying architecture and functionality of products and technologies, highly integrated and aggregated innovation capabilities can significantly enhance the firm’s innovation performance, while relying on the collaboration with external partners does not significantly improve such innovation performance. This made little expansion the existing supply chain collaboration theory – for knowledge intensive industries, centralization of the recourses will have a more positive influence on the firm’s innovation performance.